2020
DOI: 10.2298/aadm190219046d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of edge and vertex deletion on omega invariant

Abstract: Recently the first and last authors defined a new graph characteristic called omega related to Euler characteristic to determine several topological and combinatorial properties of a given graph. This new characteristic is defined in terms of a given degree sequence as a graph invariant and gives a lot of information on the realizability, number of realizations, connectedness, cyclicness, number of components, chords, loops, pendant edges, faces, bridges etc. of the family of realizations. In this paper, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It is shown that Ω(G) � 2(m − n) and therefore it is always an even number. It is shown that the omega characteristic gives us very powerful information about cyclicness and connectedness of all the realizations of a given degree sequence (see, e.g., [9]). In brief, it is shown that all realizations of a degree sequence D with Ω(D) ≤ − 4 must be disconnected; each connected realization of a degree sequence D with Ω(D) � −2 must be a tree; each connected realization of a degree sequence D with Ω(D) � 0 must be a unicyclic graph; each connected realization of a degree sequence D with Ω(D) � 2 must be a bicyclic graph, etc.…”
Section: Omega Index and Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that Ω(G) � 2(m − n) and therefore it is always an even number. It is shown that the omega characteristic gives us very powerful information about cyclicness and connectedness of all the realizations of a given degree sequence (see, e.g., [9]). In brief, it is shown that all realizations of a degree sequence D with Ω(D) ≤ − 4 must be disconnected; each connected realization of a degree sequence D with Ω(D) � −2 must be a tree; each connected realization of a degree sequence D with Ω(D) � 0 must be a unicyclic graph; each connected realization of a degree sequence D with Ω(D) � 2 must be a bicyclic graph, etc.…”
Section: Omega Index and Fundamentalsmentioning
confidence: 99%
“…where c(G) is the number of components of G. For more properties of the omega index, see [10,11]. e effect of edge and vertex deletion on the omega index is studied in [9]. Next, we obtain the number of pendant vertices of a caterpillar tree which consists of a main path so that all vertices are having maximum distance 1 from the path.…”
Section: Omega Index and Fundamentalsmentioning
confidence: 99%
“…For convenience, the omega invariant of a realization G of D is also denoted by Ω( ). Some properties of Ω can be found in [1,2,3,4,6]. We recall some very important properties of it here.…”
Section: Invariantmentioning
confidence: 99%
“…A degree sequence is = {1 ( 1 ) , 2 ( 2 ) , 3 ( 3 ) , . .…”
Section: Introductionmentioning
confidence: 99%
“…Let G be a realization of a degree sequence D. We recall the definition and some properties of Ω(G) from [5,[7][8][9][10]. The number a 1 of leaves of a tree T is…”
Section: Fundamentals and ω Invariantmentioning
confidence: 99%